Perceptions of Strategies and Intervention Approaches for HIV Self-Management among Ugandan Adolescents: A Qualitative Study. (28th January 2019) - Mutumba, Massy; Mugerwa, Henry; Musiime, Victor; Gautam, Anudeeta; Nakyambadde, Hellen; Matama, Christine; Stephenson, Rob
The heightened vulnerability of adolescents to poor HIV care outcomes underscores the need for interventions that create and promote HIV self-management behavioral skills. Adolescents living with HIV (ALHIV) experience a complex array of physical, emotional, and social challenges that constrain their self-care, but the majority of existing psychosocial programs focus primarily on medication adherence. Understanding adolescents' self-care needs, challenges, and preferences is necessary for developing effective culturally relevant interventions. The involvement of caregivers and stakeholders is also critical to realizing positive self-care outcomes. This article presents the findings from focus group discussions with ALHIV, caregivers, and healthcare providers on self-care. The data were collected as part of formative research in the development of a self-management intervention for Ugandan ALHIV. Participants' discussions on self-care strategies and intervention approaches provide valuable insights to guide the development of interventions to promote positive HIV care outcomes among Ugandan ALHIV.